Utilization of fibers obtained by peroxyformic acid processing of broom as reinforcing agents for biocomposites - González, Daniel (2010)
Broom (Cytisus scoparius) samples were processed in media containing formic acid and hydrogen peroxide (MILOX process) to obtain cellulose-enriched solids. The chemical processing of broom samples was assessed by means of a centered, second order factorial design of experiments. Empirical models derived from the experimental data gave a close interpretation of the experimental patterns, and enabled the selection of operational conditions for achieving extensive delignification and hemicellulose removal, while minimizing the dissolution of cellulose. Broom samples processed under the selected conditions were employed to reinforce PLA composites, which were characterized mechanically and by DSC, SEM, and water absorption experiments.